Radical mediastinal lipectomy for tamponade-like cardiac physiology - Mohsyn Imran Malik; James Changhyun Jae; Osama Sedky Shehata Sefein; Raffael Pereira Cezar Zamper; A. Dave Nagpal (Journal of Cardiothoracic Surgery, 2023)
Abstract Background Re-opening the chest is an unwanted and potentially morbid complication after open heart surgery, most commonly required for refractory bleeding or tamponade. In this report, we present a unique case of a postoperative coronary artery bypass patient, demonstrating clinical features of cardiac tamponade of the right atrium and ventricle with inconclusive findings on imaging. Case presentation A 62 year-old male presented to hospital with exertional angina and a coronary angiogram found severe three-vessel coronary artery disease with preserved left ventricular function. He underwent an uncomplicated triple coronary artery bypass surgery. Over the following hours in the cardiac intensive care unit, the patient had a climbing serum lactate level and increasing vasopressor requirements. On investigations, there was evidence of compression of the right heart. The patient was taken back to the operating room where very little clot or bleeding was identified, rather there was significant amounts of mediastinal fat surrounding the heart which was subsequently resected with wide margins. The patient had complete resolution of their symptoms and an uncomplicated postoperative course thereafter. Conclusions To our knowledge, this case is the first reported occurrence of cardiac constriction from excessive mediastinal fat after open heart surgery. Identifying patients at high-risk for excessive pericardial fat, as well as considering alternative modalities of imaging appear to be the main stay in diagnosis at this point. Current treatment is a mediastinal lipectomy with wide margins, avoiding injury to surrounding structures such as the phrenic nerve and innominate vein. Future study might consider the value of prophylactic mediastinal lipectomy at time of surgery, and methods to improve detection with current and future imaging modalities.